Session 1, Panel 2, Kamis Wrang, Laura. Storytelling, Education and Children - Laura Kamis Wrang - Jarvis, Dale (2010)
Laura Kamis Wrang speaking at the 18th Annual Conference of Storytellers of Canada-Conteurs du Canada.